Integrated care pilot in north-west London: a mixed methods evaluation. - Curry,N; Harris,M; Gunn,LH; Pappas,Y; Blunt,I; Soljak,M; Mastellos,N; Holder,H; Smith,J; Majeed,A; Ignatowicz,A; Greaves,F; et al. (Int J Integr Care, 2013)
INTRODUCTION: This paper provides the results of a year-long evaluation of a large-scale integrated care pilot in north-west London. The pilot aimed to integrate care across primary, acute, community, mental health and social care for people with diabetes and/or those aged 75+ through care planning, multidisciplinary case reviews, information sharing and project management support. METHODS: The evaluation team conducted qualitative studies of change at organisational, clinician and patient levels (using interviews, focus groups and a survey); and quantitative analysis of change in service use and patient-level clinical outcomes (using patient-level datasets and a matched control study). RESULTS: The pilot had successfully engaged provider organisations, created a shared strategic vision and established governance structures. However, the engagement of clinicians was variable and there was no evidence to date of significant reductions in emergency admissions. There was some evidence of changes in care processes. CONCLUSION: Although the pilot has demonstrated the beginnings of large-scale change, it remains in the early stages and faces significant challenges as it seeks to become sustainable for the longer term. It is critical that National Health Service managers and clinicians have realistic expectations of what can be achieved in a relatively short period of time.